Screening for colorectal cancer in defunctioned colons. (December 2018) - Akbar, Fayyaz; Quyn, Aaron; Steele, Robert
Objectives: Population-based colorectal (bowel) cancer screening using faecal occult blood tests leads to a reduction in cause-specific mortality. However, in people where the colon is defunctioned, the use of standard faecal occult blood test is not appropriate. The aim of this study was to examine the current trends of clinical practice for colorectal cancer screening in people with defunctioned colons. Methods: An online survey was performed using SurveyMonkey. All members of the Association of Coloproctology of Great Britain and Ireland were invited by email to participate. Reminders were sent to non-responders and partial responders till six weeks. All responses were included in our analysis. Results: Of the 206 (34.59%) questionnaires completed, all questions were answered in 110 (55.8%). Among responders, 94 (85.4%) were colorectal consultant surgeons, 72% had worked in their current capacity for more than five years, and 105 (50.9%) had encountered colorectal cancer in defunctioned colons during their career. Some 72.2% of responders stated that a screening test for colorectal cancer in patients with defunctioned colons was currently not offered, or that they did not know whether or not it was offered in their area. Conclusions: Bowel screening in the United Kingdom is currently not offered to 72.2% of the age appropriate population with defunctioned colons. Among responding colorectal surgeons, 50% had encountered colorectal cancer in such patients. There is considerable variability in clinical practice regarding the optimal age for onset of screening, time interval, and the optimal modality to offer for screening in such cases.